Tracheostomy in the pediatric trisomy 21 population. (January 2021) - Hamill, Chelsea S.; Tracy, Meghan M.; Staggs, Vincent S.; Manimtim, Winston M.; Neff, Laura L.; Jensen, Daniel R.
Abstract: Introduction: Tracheostomy in children is often performed to alleviate airway obstruction (AO) or to facilitate long-term ventilator support due to respiratory failure of various etiologies, such as heart failure, and postoperative respiratory failure. Although many of these pathologies are common among trisomy 21 patients, tracheostomy rates among this population have not previously been reported. The aim of our study was to determine the incidence of trisomy 21 patients undergoing tracheostomy. Secondary objectives include decannulation rates and mortality associated with tracheostomy. Materials and methods: A retrospective cohort study was conducted on pediatric trisomy 21 patients undergoing tracheostomy between 2004 and 2013. Results: Twenty patients underwent tracheostomy at a median age of 7.1 months (interquartile range [IQR] = 3.5, 21.3). The estimated incidence of tracheostomy in trisomy 21 patients among our tracheostomy population was 1.7% (20/1173) over 10 years. The most common indications were airway obstruction (AO) (55%), cardiac/pulmonary respiratory failure (CRF) (25%), or both (20%). Overall mortality was 30%, much lower among AO patients (9%) than CRF (40%) or both (60%), ( P  = 0.029). Nine patients (45%) were successfully decannulated, with median duration of cannulation of 2.2 years (IQR = 1.7, 3). Conclusions: This study suggests a rate of tracheostomy in the pediatric trisomy 21 population approximately 3 times that of the general pediatric population. Over half in this cohort underwent tracheostomy for isolated AO, while the general pediatric tracheostomy population demonstrates a much higher prevalence of prematurity-related CRF. Overall mortality rate and decannulation rate approximated that of the general pediatric tracheostomy population, although outcomes were significantly poorer among patients trisomy 21 patients undergoing tracheostomy for CRF.